These designs hold water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Establishing and managing water points for village livestock: A guide for rural extension workers in the sudano-sahelian zone By A Teyssier, Agrodok series, Agromisa-CIRAD-CTA, 2000. 75 pp. ISBN 9907246 90 CTA number 1021. 5 Credit points